PENGARUH MOTIVASI INTRINSIK, KOMPETENSI RELASIONAL, KOMPETENSI KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BAPPEDA KABUPATEN BIMA - Muhamad Akbar Umar; Meutia Meutia; Heriani Heriani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This research aims to test and analyze the effect of intrinsic motivation, Competence of Communication and Work Environment toward employee performance at Bappeda Office of Bima Regency. Population in this research is 64 employees of Staffing at Bappeda Office of Bima Regency. Data analysis was undertaken using statistical programme of SPSS and. The analysis method was multiple linear regression. The method used in this research is quantitative research methods. Independent variables (independent variables) in this study is Intrinsic Motivation (XI), Competence of Relational (X2), Competence of Communication (X3), and Work Environment (X4). Meanwhile, the dependent variable (the dependent variable) is the employee's performance (Y). Sampling technique used in this research was sample saturated technique. The results showed that (1) Intrinsic Motivation have positive effect and no significant effect toward job satisfaction, (2) Competence of Relational have negative effect and significan effect toward job satisfaction, (3) Competence of Communication have negative effect and no significant toward job satisfaction, and (4) Work Environment have positive effect and no significant toward job satisfaction.